The asymmetric effects of monetary policy : Malaysia evidence - Abd Alla, Izzeldin E. (Kulliyyah of Economics and Management Sciences, International Islamic University Malaysia, 2000)
The relationship between output and money supply has been the subject of many empirical studies, which failed however, to take into account the distinction between positive and negative growth in money supply. Trus study explores whether positive and negative growth in money supply has symmetric effects on output in Malaysia. It attempts to test the hypothesis that positive growth in money supply does not have an effect on output, while negative growth in money supply significantly reduces output. All models used m the study are based on Granger framework, and are estimated using the method of Ordinary Least Squares (OLS). Using Granger causality tests at the preliminary analysis, the study recorded that the negative growth in money supply leads, while the positive growth lags output. In addition, the findings implied that the output effects of money supply in Malaysia are asymmetric. This result is robust across all the different specifications used in the study. The results of this paper indicate that at times of recession, expansionary monetary policy would not help in heating the economy, as the effects of the positive growth in money supply appeared to be statistically not different from zero. Moreover, the increase in money supply could fuel inflation, which would require a more sigmficant offsetting future monetary contraction, an act that might prove to be counter-productive The results also imply that monetary policy could be used to cool down the economy if it is booming too fast. Trus study focused on monetary policy as an independent measure, however, there are other policies, which may also influence or change the results. Such influences might be the subject of further invetigation in future